AN INVESTIGATION ON LEAN PRACTICES AND SUSTAINABLE DEVELOPMENT - SUBASHINI, Dr.G.S. (International Journal of Psychosocial Rehabilitation, 2020)
This paper seeks to reflect on Lean manufacturing's significance in achieving an organization's sustainable development. Customer satisfaction through improved quality, reduced costs, shortened delivery lead times and good communication is the secret to achieving sustainable development. Lean Manufacturing philosophies help managers recognize and eliminate waste at all organizational levels. Lean concepts are well established across waste disposal with recorded savings and productivity improvements. Most companies have found that "clean" or ecological quality is improved by a by-product of lean concepts, even if lean practices have not been implemented for environmental reasons. This paper analyzes the relationship between lean and sustainable development practices. Data were collected and analyzed using SPSS through a survey of 53 manufacturing firms in Chennai. Eighteen lean facilities have been reduced to four factors: 1 Lean-Agile Leadership.2Environmental factor3)Economic and 4)Social factor. The results indicate that lean activities influence sustainable output positively and significantly. Such findings have significant implications for improving manufacturing firms ' sustainable efficiency through lean manufacturing practices.